Entrepreneurship from an Islamic perspective - Gümüsay, A (Springer Netherlands, 2014)
Research about the role of religion in entrepreneurship and more broadly management is sparse. In this conceptual article, we complement existing entrepreneurship theory by examining entrepreneurship from an Islamic perspective (EIP). EIP is based on three interconnected pillars: the entrepreneurial, socio-economic/ethical, and religio-spiritual. We outline how Islam shapes entrepreneurship at the micro-, meso-, and macro-level, indicate how Islam may be considered an entrepreneurial religion in the sense that it enables and encourages entrepreneurial activity, review research streams interlinking Islam with entrepreneurship and management and outline promising research approaches.